Füstbe ment régiók? - Nemes Nagy József (Közép-európai Monográfiák, 2017)
The introductory chapter of the essay provides an overview of some fundamental issues and debates around the theory of social space. It discusses the dual nature of space (continuous and divided up at the same time), the consequent challenges of spatial division, and the relation of the region, a definitely social category, to the landscape, more attached to physical and environmental categories. Among the complex processes and ideas that have emerged since the transition in 1989-90, the paper analyses the career 'Europe of the Regions' made as concept, the illusions the concept brought into being, and how it has almost profoundly disappeared by now from the professional discourse. East Central Europe in general has made no considerable progress towards regional decentralisation, thus, a stronger competence of the regions in issues of control. Attachment to Europe and the European Union largely becomes manifest in a single issue, the willingness to gain support from EU funds and to distribute it, predominantly through centralised mechanisms. This feature is characteristic not only of the current regime of politics and control in Hungary, but of all countries in the Carpathian Basin. First priorities are to strengthen cohesion within the nation-states and to promote centralised mechanisms of control. A tanulmány bevezető fejezete a társadalmi térelmélet néhány alapvető kérdését, dilemmáját tekinti át: a tér folytonosságának és osztottságának kettőségét, a térfelosztások ebből fakadó nehézségeit valamint a határozottan társadalmi töltetű régió és az erősebben a természeti, környezeti elemekhez kötődő táj fogalmát és viszonyát. A rendszerváltozás óta eltelt időszak összetett folyamatai, eszmerendszeri közül értelmezi a „a régiók Európája" - gondolat hazai életútját, az ehhez kötődő illúziókat és a fogalom lényegében teljes eltűnését a szakmai közbeszédből. Kelet-Közép-Európában lényegében nem történet érdemi előrelépés a területi decentralizáció, a téregységek irányítási kompetenciáinak erősödése irányába. E térségben az Európához (az Európai Unióhoz) való tartozás, kötődés lényegében egyetlen momentumra szükül: a közösségi támogatási források megszerzésére és ezek, jellemzően központilag vezérelt szétosztására. Ez a jegy nem csak az aktuális magyar irányítási-politikai szisztéma sajátja, hanem a Kárpát-medence országainak mindegyikérejellemző: a (többségi) nemzetállami kohézió erősítése és az ehhez kötődő centralizált irányítás a privilegizált szempont.